1990
DOI: 10.1177/000348949009901011
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Middle Ear Vascular Leakage Sites in Experimental Otitis Media

Abstract: The site of leakage in middle ear vessels was determined and characterized in experimental otitis media in rats. Middle ear effusion was induced by intravenous administration or local application in the tympanic bulla of substance P (SP), acetylcholine, and histamine. In another experiment, a 14 degrees C airstream was blown into the external auditory canal. Colloidal carbon was used to trace leakage sites at the light and electron microscopic levels. All mediators tested and the 14 degrees C airstream resulte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Morphological studies have also noted the presence of lymphatics in the ME based (Lim and Hussl, 1975), and drainage from the ME to lymph nodes of the neck has been demonstrated (Galich, 1973;Lim and Hussl, 1975), validating lymphatic endothelial cells of Cluster 9 cells. The documentation of capillaries and post-capillary venules in the ME (e.g., Goldie and Hellström, 1990) makes the observation of pericytes in Cluster 13 unremarkable. Gene expression related to hypoxia, contractility and water permeability are consistent with pericyte regulation of vascular tone, based on oxygen tension, and fluid entry into the ME.…”
Section: Vascular Cellsmentioning
confidence: 99%
“…Morphological studies have also noted the presence of lymphatics in the ME based (Lim and Hussl, 1975), and drainage from the ME to lymph nodes of the neck has been demonstrated (Galich, 1973;Lim and Hussl, 1975), validating lymphatic endothelial cells of Cluster 9 cells. The documentation of capillaries and post-capillary venules in the ME (e.g., Goldie and Hellström, 1990) makes the observation of pericytes in Cluster 13 unremarkable. Gene expression related to hypoxia, contractility and water permeability are consistent with pericyte regulation of vascular tone, based on oxygen tension, and fluid entry into the ME.…”
Section: Vascular Cellsmentioning
confidence: 99%
“…The pars tensa is the connective tissue layerofthe auditorycanal of the TM. Them ajority of the transparent portion of the pars tensa is devoid of blood vessels (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…NumberofapparentlyclosedTMs in relation to the totalnumberofTMs examined. At eachexamination time point(4,8,11,16,36, 50, 72 and 143 days), TMs from both earsof9,9,9,7,5,5,5and 5wtmice and 5, 5, 8, 8, 8, 13, 13 and 8plg-deficient mice were analyzed. **Inplg-deficient mice all of theappar-entlyclosedTMs were either coveredbycrusts or hadanopaque and thick appearance.…”
mentioning
confidence: 99%
“…Middle ear effusions observed in the control group animals have also been demonstrated by other investigators and it has been suggested that this is because of an increased permeability in various regions of the middle ear. The major route for increasing vessel permeability is the opening of interendothelial junctions (Hellstrom et al, 1982;Udmann et al, 1985;Widemar et al, 1985;Goldie et al, 1989;Goldie and Hellstrom, 1990). It has been reported that vasoactive neuropeptides and particularly substance P, allow gaps the transport of fluid into the middle ear cavity by forming of interendothelial gaps (Hellstrom et al, 1982 Hellstrom, 1988;Goldie and Hellstrom, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…The major route for increasing vessel permeability is the opening of interendothelial junctions (Hellstrom et al, 1982;Udmann et al, 1985;Widemar et al, 1985;Goldie et al, 1989;Goldie and Hellstrom, 1990). It has been reported that vasoactive neuropeptides and particularly substance P, allow gaps the transport of fluid into the middle ear cavity by forming of interendothelial gaps (Hellstrom et al, 1982 Hellstrom, 1988;Goldie and Hellstrom, 1990). In the present study no significant difference between the two groups in respect of vasodilatation was found whereas the presence of effusion in only one case of the group pre-treated with capsaicin supports the views of the authors suggesting that capsaicin can prevent the increase in vascular permeability by decreasing the opening of the interendothelial junctions (Hellstrom et al, 1982;Gyorfl et al, 1993;Norlander et al, 1996).…”
Section: Discussionmentioning
confidence: 99%